2013
DOI: 10.1002/ijc.28013
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochic acid‐induced upper tract urothelial carcinoma in Taiwan: Clinical characteristics and outcomes

Abstract: Aristolochic acid (AA), a component of all Aristolochia‐based herbal medicines, is a potent nephrotoxin and human carcinogen associated with upper urinary tract urothelial carcinoma (UUC). To investigate the clinical and pathological characteristics of AA‐induced UUC, this study included 152 UUC patients, 93 of whom had been exposed to AA based on the presence of aristolactam‐DNA adducts in the renal cortex. Gene sequencing was used to identify tumors with A:T‐to‐T:A transversions in TP53, a mutational signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 26 publications
6
110
0
1
Order By: Relevance
“…There is possible correlation between UUC and aristolochic acid (AA), a component of all aristolochia-based herbal medicines. AA exposure was associated with an increased risk for developing synchronous bilateral and metachronous contralateral UUC (30). Following metabolic activation, AA reacts with DNA to form aristolactam-DNA adducts, which then results in a unique mutation in the TP53 tumour-suppressor gene in the urothelium (31).…”
Section: Bladder Cancermentioning
confidence: 99%
“…There is possible correlation between UUC and aristolochic acid (AA), a component of all aristolochia-based herbal medicines. AA exposure was associated with an increased risk for developing synchronous bilateral and metachronous contralateral UUC (30). Following metabolic activation, AA reacts with DNA to form aristolactam-DNA adducts, which then results in a unique mutation in the TP53 tumour-suppressor gene in the urothelium (31).…”
Section: Bladder Cancermentioning
confidence: 99%
“…Associated comorbidities, such as diabetes mellitus, hypertension, hyperlipidemia, coronary artery disease (CAD), renal disease, liver cirrhosis, and organ transplantation, diagnosed or performed after 2000 were ascertained by using diagnostic codes. Aristolochic acid (AA) is a nephrotoxicant suggested to be associated with AA nephropathy (AAN) and upper urothelial tract cancer [19] . Although RCC has not been linked to AAN and AA exposure previously, some recent studies implicate the potential role of AA in RCC development [20,21] .…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Chen et al 21 compared the clinical and pathological characteristics of AA-induced versus non-AAinduced upper urinary tract urothelial cancer and found that patients with AA-induced cancer had a significantly higher risk of contralateral recurrence compared with patients with non-AA-induced cancer.…”
Section: Discussionmentioning
confidence: 99%